Modification of polyethylene terephthalate by atmospheric pressure dielectric barrier discharge (DBD) in view of improving the polymer wetting properties - Kostov, K. G. [UNESP]; dos Santos, A. L. R. [UNESP]; Nascente, P. A. P.; Kayama, M. E. [UNESP]; Mota, Rogério Pinto [UNESP] (Iop Publishing Ltd, 2012)
Surface treatment of polymers by discharge plasmas has increasingly found industrial applications due to its capability of modifying uniformly the surface without changing the material bulk properties. This work deals with surface modification of polyethylene terephthalate (PET) by a dielectric barrier discharge (DBD) at atmospheric pressure. The treatments were conducted in air, nitrogen or argon plasma. The polymer surface was characterized by contact angle measurement, X-ray photoelectron spectroscopy (XPS) and atomic force microscopy (AFM). The results show that the plasma treatment introduces oxygen-and nitrogen-related polar groups on the polymer surface and promotes the surface roughening. Both plasma-induced surface modifications contribute to the enhancement of the polymer wettability.